Diversity and conservation status of small mammals in Kelantan, Malaysia - Jayaraj V.K; Faisal A.A. Khan; Isham Azhar; Ean WeeChen; Mohd Rohanif Mohd Ali; Amirrudin Ahmad; Azrinaaini Mohd Yusoff (Songklanakarin Journal of Science and Technology (SJST), 2016)
There is little information and research on the diversity of the small mammals in Kelantan. Thus, a series of wildlife surveys were done at five localities in Kelantan to further elucidate the diversity of small mammals in this state. There were 39 species of small mammals recorded, 13 of these are new records for Kelantan. This significantly increased the known diversity of small mammals from 71 to 84 species. However, the diversity of small mammals in Kelantan is still underrepresented and further surveys are needed to add more information to the current knowledge.